The Innovative Control Management of Travel Companies - Bolgova, Viktoriya V.; Makushkin, Sergey A.; Povorina, Elena V.; Duplij, Elena V.; Demchenko, Tatiana S. (International Review of Management and Marketing, 2016)
Tourist business is considered to be the global socio-economic phenomenon of the modern world, society. Half a billion of tourists, vacationers, travelers spend more than one-third of a trillion dollars on trips. The relevance of the study of innovation processes of the governance management, the policy of maintenance of company’s strategies – the mission of the tourist business is dictated by practical and scientific considerations. In practical terms, the rapidly emerging industry of tourism business, using the obvious, lying on the surface the reserves of development require the latest momentum in the process of transformation and change, in search of innovation to justify their position in the competition. Especially big risks take on the organization, realizing the strategic guidelines. Russian tourist industry, forming its own way, needs a generalization of accumulated experience in the formation of a unified policy of innovation management and its application. This article contains the information about the directions of formation of innovative activity in the sphere of tourism services and in the literate application of it in the enterprises of this industry. Also it informs the main of innovative technologies of the governance management, its content, application and effectiveness. Keywords: innovation, tourism, management, governance, globalization, competitiveness and profits JEL Classifications: M31, O35, M14, O32